Effect Effect Of Kombucha Tea Fermentation From Green Tea And Red Dragon Fruit Skins On Antioxidant Activity And Organoleptic - Salsabilah, Chiara Elvira; Handayani, Septy (ARGIPA (Arsip Gizi dan Pangan), 2024)
About 30-35% of red dragon fruit presented in the form of fruit skin is rarely used by the community and thrown away as waste. It can have the potential to be a source of natural antioxidants due to its high antioxidant activity. This study included the antioxidant activity and organoleptic tests of kombucha tea from green tea and red dragon fruit skin based on fermentation time. The time used was F1= 1 day, F2 = 3 days, F3 = 5 days, F4 = 7 days by design Quasi-Experimental. Red dragon fruit skin samples were obtained from plantation of Cemoro Hamlet, Songgon District, Banyuwangi Regency and there were 30 untrained panelists (19-23 years) as organoleptic test samples. The concentration used in making kombucha tea is 50 g of green tea and 15 g of red dragon fruit skin extract (30% of 50 g of green tea). Testing of antioxidant activity using the DPPH method and analyzed using One Way ANOVA. The organoleptic test used the hedonic method and the data were analyzed using Friedman then proceed with Wilcoxon Sign Rank Test. The results of the research on the antioxidant activity of each sample have an average of F1= 64,34%; F2= 65,9%; F3= 65,8% and F4= 65,17%. Of the four samples there was no significant difference, so there was no sample with the most optimum activity. The most preferred by the panelists is F1. Thus, the best formulation recommended is F1 with antioxidant activity of 64,34%.